Nanocrystals: A Versatile 'Click Chemistry' Route to Size‐Restricted, Robust, and Functionalizable Hydrophilic Nanocrystals (Small 14/2015). Issue 14 (April 2015) - Bian, Tong; Wang, Chao; Lu, Zhenda; Xie, Renguo; Yang, Qing‐Zheng; Wu, Li‐Zhu; Tung, Chen‐Ho; Liu, Zhuang; Yin, Yadong; Zhang, Tierui
<x xml:space="preserve">Abstract</x> A size‐restricted and robust hydrophilic nanocrystal obtained via a facile and versatile addition‐crosslinking route is described on page 1644 by T. Zhang and co‐workers. Due to the monolayer of cross‐linked polymer on the surface, these hydrophilic nanocrystals show excellent stability without a significant increase in the hydrodynamic sizes after modification. The nanocrystals can also be further functionalized for various applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>